Protecting the Spanish Woman: Gender Identity and Empowerment in María de Zayas’s works de Xabier Granja IBARRECHE - Brown, Katherine (Monteagudo. Revista de Literatura Española, Hispanoamericana y Teoría de la Literatura, 2024)
Reseña de Granja Ibarreche, Xabier: Protecting the Spanish Woman: Gender Identity and Empowerment in María de Zaya´ s works. University of Nevada Press, 2023.